Outstanding pre-soviet period representatives of pedagogy on the significance of drawing in educating of a personality - Morkytė, J. (Psichologija, 1963)
Solving the questions of educating a harmonious personality, the classics of pedagogy J. A. Komensky, Z. Z. Rousseau, D. Lock, l. G. Pestalozzi assigned a significant role to drawing. Education by drawing was emphasized in the development of children’s senses, perception and the benefits of drawing skills in practical life.Especially deeply the aesthetic education was understood by the famous Russian pedagogues L. Tolstoy and K. Ušinsky. They required to raise not only popular talents, but also to provide aesthetical education to all children of the nation, by engraining in them graphical expression skills, developing aesthetic feelings, imagination necessary to a versatile educated personality.
Keywords: teaching of drawing; history of pedagogy